قرآن وسنت سے اخذ واکتساب میں فقہاء مالکیہ کا مؤقف: Position of Mālikī Jurists in deriving and acquiring arguments from Quran and Sunnah (Al-Qamar, 2020)
The Quran commands obedience to God and his messenger (ﷺ) and there are permanent texts in the Quran for on the subject. Allah has declared obedience to the messenger (ﷺ) as his obedience. Different jurists have explained and used the principles of derivation of arguments from Quran and Sunnah, from different angles. This article contains the views of Mālkī jurists about deriving and acquiring arguments from Quran and Sunnah.
Keywords: Quran; Sunnah; Jurists; Mālikī